Arterial occlusive events in chronic myeloid leukemia patients treated with ponatinib in the real‐life practice are predicted by the Systematic Coronary Risk Evaluation (SCORE) chart. Issue 3 (17th April 2019) - Caocci, Giovanni; Mulas, Olga; Abruzzese, Elisabetta; Luciano, Luigiana; Iurlo, Alessandra; Attolico, Immacolata; Castagnetti, Fausto; Galimberti, Sara; Sgherza, Nicola; Bonifacio, Massimiliano; Annunziata, Mario; Gozzini, Antonella; et al.
Abstract: Arterial occlusive events (AOEs) represent emerging complications in chronic myeloid leukemia (CML) patients treated with ponatinib. We identified 85 consecutive CML adult patients who were treated with ponatinib in 17 Italian centers. Patients were stratified according to the Systematic Coronary Risk Evaluation (SCORE) assessment, based on sex, age, smoking habits, systolic blood pressure, and total cholesterol levels. The 60‐month cumulative incidence rate of AOEs excluding hypertension was 25.7%. Hypertension was reported in 14.1% of patients. The median time of exposure to ponatinib was 28 months (range, 3‐69 months). Patients with a high to very high SCORE risk showed a significantly higher incidence rate of AOEs (74.3% vs 15.2%, P < 0.001). Patients aged ≥60 years showed a significantly higher incidence rate of AOEs (51.5% vs 16.9%, P = 0.008). In multivariate analysis, no association was found between AOEs and positive history of CV disease, age, dose of ponatinib, previous exposure to nilotinib, and comorbidities. Only the SCORE risk was confirmed as a significant predictive factor ( P = 0.01; HR = 10.9; 95% C.I. = 1.7‐67.8). Patients aged ≥60 years who were treated with aspirin had a lower incidence rate of AOEs (33.3% vs 61.8%). Among the 14 reported AOEs, 78.6% of them showed grade 3 to 4 toxicity. This real‐life study confirmed the increased incidence of AOEs in CML patients treated with ponatinib, with high to very high SCORE risk. We suggest that patients aged ≥60 years who were treated with ponatinib should undergo prophylaxis with 100 mg/day of aspirin. Our findings emphasize personalized prevention strategies based on CV risk factors.